2022
DOI: 10.1245/s10434-022-12387-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Oncological Outcomes After Preoperative FOLFIRINOX Chemotherapy in Resected Pancreatic Cancer: An International Multicenter Cohort Study

Abstract: Background Preoperative FOLFIRINOX chemotherapy is increasingly administered to patients with borderline resectable (BRPC) and locally advanced pancreatic cancer (LAPC) to improve overall survival (OS). Multicenter studies reporting on the impact from the number of preoperative cycles and the use of adjuvant chemotherapy in relation to outcomes in this setting are lacking. This study aimed to assess the outcome of pancreatectomy after preoperative FOLFIRINOX, including predictors of OS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These results have been further corroborated by several cohort studies, matched-propensity analyses, systematic reviews, and meta-analyses comparing neoadjuvant therapy approaches to up-front surgical approaches, although the studies are limited due to variability in definitions of resectability and treatment regimens 38,41–61 . A meta-analysis of 27 studies and 63,151 patients, including 8461 who received neoadjuvant chemotherapy and 54,690 patients who received up-front surgery, demonstrated that neoadjuvant chemotherapy resulted in a better OS (hazard ratio [HR]: 0.72, 95% CI: 0.69-0.76) and improved R0 resection rate (HR: 0.62, 95% CI: 0.60-0.65) compared with up-front surgery 41 …”
Section: Summary Of Literature Reviewmentioning
confidence: 83%
“…These results have been further corroborated by several cohort studies, matched-propensity analyses, systematic reviews, and meta-analyses comparing neoadjuvant therapy approaches to up-front surgical approaches, although the studies are limited due to variability in definitions of resectability and treatment regimens 38,41–61 . A meta-analysis of 27 studies and 63,151 patients, including 8461 who received neoadjuvant chemotherapy and 54,690 patients who received up-front surgery, demonstrated that neoadjuvant chemotherapy resulted in a better OS (hazard ratio [HR]: 0.72, 95% CI: 0.69-0.76) and improved R0 resection rate (HR: 0.62, 95% CI: 0.60-0.65) compared with up-front surgery 41 …”
Section: Summary Of Literature Reviewmentioning
confidence: 83%
“…In 8 of 22 studies (36.4%), R0 was defined as absence of tumour cells at the resection margin (R0 narrow = R0 direct) with R1 corresponding to presence of tumour cells directly at the resection margin (R1 narrow = R1 direct) 13 , 15 , 17 , 34 38 . In the remaining 14 studies (63.6%), R0 was defined as tumour-free margin greater than 1 mm (R0 wide = R0 >1 mm) and R1 as tumour cells less than or equal to 1 mm from the margin (R1 wide = R1 ≤1 mm) 6 , 11 , 12 , 14 , 19 , 20 , 39 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In 14 studies with a total of 3284 patients, HR for median OS after R0 greater than 1 mm versus R1 less than or equal to 1 mm resection were reported with a pooled estimate of 22% (95% CI 7–70%) for R1 resections 6 , 11 , 12 , 14 , 19 , 20 , 39 46 . Using univariable data from 13 eligible studies, meta-analysis revealed that R0 greater than 1 mm resection was significantly associated with prolonged OS compared with R1 less than or equal to 1 mm resection (pooled HR 1.76, 95% CI 1.57–1.97; P <0.00001), with I 2 = 0% 11 , 15 , 34 , 35 , 37 , 38 , 41 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this symposium was to bring together experts in the field of locally advanced pancreatic cancer with western and eastern experience to reach a consensus opinion of which factors should be included to address updated guidelines on resectabilty in pancreatic cancer that reflects recent developments in defining resectability after NAT. This is particularly important as we continue to accumulate evidence supporting NAT for borderline resectable pancreatic cancer ( 4 , 5 ).…”
mentioning
confidence: 99%
“…Although promising, the study was limited to 20 patients and larger studies are required to confirm these findings. The identification of patients with fibrosis at the resection margin rather than viable tumour would facilitate the selection of those likely to undergo a R0 resection which is associated with improved survival ( 5 ).…”
mentioning
confidence: 99%